HUBUNGAN ANTARA DUKUNGAN SOSIAL GURU DAN PERILAKU HIDUP SEHAT DI SEKOLAH DASAR - Eny Supriyati Rosyidatun; Teguh Supriyadi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2022)
Elementary school students' healthy behavior in school is still facing problems. One of the indications is the presence of poisoning incidents at school. The role of teachers in elementary schools is very strategic in developing healthy behaviors for students in schools. One of the roles of the teacher is to provide social support to students. The purpose of this study is to determine the relationship between teacher social support and healthy behaviors in elementary school students. This research was conducted in two elementary schools around Ciputat Market, South Tangerang City, Banten Province. This research is a quantitative study using a survey method. The study population was made up of elementary school students. The sample for this research is high-grade students. A questionnaire in Google Forms format was used to collect data. The data analysis used was Spearman's rho correlation. The finding of the study is that there is a relationship between the teachers’ social support in the students’ perception and the healthy behavior of elementary school students at school. The socio-ecological model describes the important role of the social environment in shaping behavior and shows its potential for behavior change. In this case, teacher social support plays a key role in influencing the outcomes of elementary students' healthy behavior in schools. The conclusion that can be drawn from the findings is that in developing healthy behavior for elementary school students in schools, the teachers’ social support factor needs to be considered.AbstrakPerilaku hidup sehat siswa di sekolah dasar masih menjadi persoalan. Hal ini diindikasikan dengan ditemukan peristiwa keracunan di sekolah. Peran guru di SD sangat strategis dalam mengembangkan perilaku hidup sehat siswa di sekolah. Salah satu peran guru adalah memberikan dukungan sosial kepada siswanya. Penelitian ini bertujuan mengetahui hubungan antara dukungan sosial guru dan perilaku hidup sehat siswa SD di sekolah. Penelitian ini bertempat di dua SD sekitar Pasar Ciputat, Kota Tangerang Selatan, Provinsi Banten. Penelitian ini adalah penelitian kuantitatif dengan menggunakan metode survei. Populasi penelitian ini adalah siswa SD. Sampel penelitian ini adalah siswa kelas tinggi. Data dikumpulkan melalui kuesioner dalam format google form. Analisis data yang digunakan adalah korelasi Spearman’s rho. Temuan penelitian adalah terdapat hubungan antara dukungan sosial guru menurut persepsi siswa dan perilaku hidup sehat siswa SD di sekolah. Model sosial-ekologi menjelaskan peran penting lingkungan sosial dalam membentuk perilaku dan menunjukkan potensi untuk terjadinya perubahan perilaku. Dalam hal ini, dukungan sosial guru memainkan peran kunci dalam mempengaruhi perilaku hidup sehat siswa SD di sekolah. Kesimpulan yang dapat ditarik dari hasil temuan adalah bahwa dalam mengembangkan perilaku hidup sehat siswa SD di sekolah, faktor dukungan sosial guru perlu dipertimbangkan.